Effects of developed thyme and oregano essential oil formulations on Monilinia laxa and Monilinia fructicola - Tanović, Brankica; Hrustić, Jovana; Mihajlović, Milica; Grahovac, Mila; Stevanovic, Marija; Gašić, Slavica (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2020)
Essential oils have been well-known for their antimicrobial properties for a very long time. Some of them have been effectively used in human medicine for decades. Our earlier investigation revealed a great potential of thyme and oregano essential oils as crop protectants against some postharvest fruit pathogens. The effects of formulated thyme and oregano essential oils on Monilinia laxa and Monilinia fructicola were studied in vitro and in vivo. In vitro antagonistic assays were performed on solidified PDA medium usinga slightly modified agar overlay technique, while in vivo experiments were conducted on inoculated apple fruits. In vitro essays showed that the developed formulations (emulsifiable concentrates - EC) significantly inhibited the mycelial growth of Monilinia spp. Experiments in vivo, performed on inoculated apple fruits, revealed that the developed formulations provided a significant level of Monilinia spp. suppression. To our knowledge, another EC formulation of oregano essential oil intended for use in Monilinia spp. control has never been developed before. The presented results are initial findings and evaluation of the activity of the developed products should therefore proceed under field conditions to determine their efficacy and activity spectrum, and to estimate economic aspects of their use.
Keywords: essential oils, biopesticides, postharvest fruit pathogens, Monilinia